Selection of HIV-Specific Immunogenic Epitopes by Screening Random Peptide Libraries with HIV-1-Positive Sera - Scala, Giuseppe; Chen, Xueni; Liu, Weimin; Telles, Jean Noel; Cohen, Oren J; Vaccarezza, Mauro; Igarashi, Tatsu; Fauci, Anthony S (The Journal of immunology (1950), 1999)
Efforts to develop a protective HIV-1 vaccine have been hindered by difficulties in identifying epitopes capable of inducing broad neutralizing Ab responses. In fact, the high mutation rate occurring in HIV-1 envelope proteins and the complex structure of gp120 as an oligomer associated with gp41 result in a high degree of antigenic polymorphism. To overcome these obstacles, we screened random peptide libraries using sera from HIV-infected subjects to identify antigenic and immunogenic mimics of HIV-1 epitopes. After extensive counterscreening with HIV-negative sera, we isolated peptides specifically recognized by Abs from HIV-1-infected individuals. These peptides behaved as antigenic mimics of linear or conformational HIV-1 epitopes generated in vivo in infected subjects. Consistent with these findings, sera of simian HIV-infected monkeys also recognized the HIV-specific epitopes. The selected peptides were immunogenic in mice, where they elicited HIV-specific Abs that effectively neutralized HIV-1 isolates. These results demonstrate that pools of HIV-1 mimotopes can be selected from combinatorial peptide libraries by taking advantage of the HIV-specific Ab repertoire induced by the natural infection.